Effect of the PREPARE intervention on sexual initiation and condom use among adolescents aged 12-14: a cluster randomised controlled trial in Dar es Salaam, Tanzania - Elia John Mmbaga; Lusajo Kajula; Leif Edvard Aarø; Mrema Kilonzo; Annegreet Gera Wubs; Sander Matthijs Eggers; Hein de Vries; Sylvia Kaaya (BMC, 2017)
Abstract Background Unsafe sexual practices continue to put adolescents at risk for a number of negative health outcomes in Tanzania. While there are some effective theory-based intervention packages with positive impact on important mediators of sexual behaviours, a context specific and tested intervention is urgently needed in Tanzania. Purpose To develop and evaluate an intervention that will have a significant effect in reducing sexual initiation and promoting condom use among adolescents aged 12-14 in Dar es Salaam, Tanzania. Design A school-based Cluster Randomised Controlled Trial was conducted during 2011-2014 in Kinondoni Municipality. Methods A total of 38 public primary schools were randomly selected, of which half were assigned to the intervention and half to the control group based on their size and geographic location. Participants were interviewed using a self-administered questionnaire at baseline before the PREPARE intervention and then, 6 and 12 months following intervention. The primary outcomes were self-reported sex initiation and condom use during the past 6 months. Data analysis was done using Generalized Estimating Equation (GEE) modelling controlling for repeated measures and clustering of students within schools. Results A total of 5091 students were recruited at baseline, and interviewed again at 6 (n = 4783) and 12 months (n = 4370). Mean age of participants at baseline was 12.4 years. Baseline sociodemographic, psychometric and behavioural characteristics did not significantly differ between the two study arms. The GEE analysis indicated that the intervention had a significant effect on sexual initiation in both sexes after controlling for clustering and correlated repeated measures. A significantly higher level of action planning to use condoms was reported among female adolescent in the intervention arm than those in the control arm (p = 0.042). An effect on condom use behaviour was observed among male adolescent (p = 0.004), but not among female (p = 0.463). Conclusions The PREPARE intervention had an effect in delaying self-reported sexual initiation among adolescents aged 12-14 in Dar es Salaam Tanzania. The intervention positively influenced action planning to use condoms for both sexes and increased actual condom use among male adolescents only. Future interventions addressing adolescent sexual and reproductive health should focus on impacting mediators of behaviour change. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12613000900718 , registered on 13 August, 2013.